Doubling the dose of budesonide versus maintenance treatment in asthma exacerbations. Issue 7 (28th June 2004) - FitzGerald, J M; Becker, A; Sears, M R; Mink, S; Chung, K; Lee, J
Abstract : Background: Previous guidelines recommend doubling the daily dose of maintenance inhaled corticosteroid to treat or prevent progression of exacerbations of asthma. Methods: Over a 6 month period a cohort of patients were evaluated prospectively and randomised in a double blind controlled trial to treatment with either a continued maintenance dose (MD) of inhaled corticosteroid or doubling the dose (DD) at the time of an exacerbation. Results: A total of 290 patients were randomised (33% male) and 98 (DD, n = 46) experienced evaluable asthma exacerbations during the study period. Mean (SD) baseline characteristics at randomisation (age 33.5 (14.0) years; forced expiratory volume in 1 second (FEV1 ) 2.8 (0.7) l; peak expiratory flow (PEF) 422.9 (110.5) l/min) were similar in both groups. In the DD group 41% of patients were considered treatment failures because they either required systemic steroids (n = 12), had an unscheduled visit to a physician (n = 1), or their asthma did not return to baseline (n = 6). This did not differ from the MD group in which 40% were treatment failures (n = 9, 0, and 12, respectively; p = 0.94). Conclusions: In patients who regularly take an inhaled corticosteroid, doubling the maintenance dose may not affect the pattern of the exacerbation.